Highly Efficient Organic Solar Cells with Improved Vertical Donor-Acceptor Compositional Gradient Via an Inverted Off-Center Spinning Method - Huang, Jiang; Carpenter, Joshua H.; Li, Chang-Zhi; Yu, Jun-Sheng; Ade, Harald; Jen, Alex K.-Y. (Advanced materials (Weinheim), 2016)
A novel, yet simple solution fabrication technique to address the trade‐off between photocurrent and fill factor in thick bulk heterojunction organic solar cells is described. The inverted off‐center spinning technique promotes a vertical gradient of the donor–acceptor phase‐separated morphology, enabling devices with near 100% internal quantum efficiency and a high power conversion efficiency of 10.95%.